2021
DOI: 10.1002/cnr2.1589
|View full text |Cite
|
Sign up to set email alerts
|

Complete and durable response of pulmonary large‐cell neuroendocrine carcinoma to pembrolizumab

Abstract: Background Pulmonary large cell neuroendocrine carcinoma (LCNEC) is a rare and aggressive tumor with a poor prognosis and standard therapy has not yet been established. Case A 65‐year‐old male with a cough for 2 months presented to our hospital. He was clinically diagnosed with non small cell lung cancer cT3N1M0 stage IIIA and underwent right pneumonectomy. The final diagnosis was pulmonary LCNEC pT3N1M0 stage IIIA. Multiple subcutaneous masses were detected 4 months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The same case report has been made for lung cancer. 9 , 10 Tumor‐infiltrating plasma cells are a favorable prognostic factor in lung cancer. 11 , 12 In various cancer types, the presence of B cells and tertiary lymphoid structures is associated with longer disease‐free and overall survival in patients treated with ICI.…”
Section: Discussionmentioning
confidence: 99%
“…The same case report has been made for lung cancer. 9 , 10 Tumor‐infiltrating plasma cells are a favorable prognostic factor in lung cancer. 11 , 12 In various cancer types, the presence of B cells and tertiary lymphoid structures is associated with longer disease‐free and overall survival in patients treated with ICI.…”
Section: Discussionmentioning
confidence: 99%
“…PD‐L1 expression on tumor cells, TILs, TLSs, and the tumor mutation burden has been reported as possible predictive biomarkers for ICI efficacy. In fact, some tumors that respond to therapy show high lymphocyte infiltration 4 . PD‐L1 is reportedly expressed in ~10% to 20% of pulmonary LCNECs 9 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study indicated that there may not be an accurate correlation between the PD‐L1 expression level and effect of ICIs 10 . Among the reported patients with LCNEC who achieved CR by ICIs, many CD138‐positive plasma cells were observed in their tumors 4 . Tumor‐infiltrating plasma cells are regarded as a favorable prognostic factor in lung cancer 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations